Efficacy and safety of robotic radical hysterectomy in cervical cancer compared with laparoscopic radical hysterectomy: a meta-analysis - Dai, Zhen; Qin, Fuqiang; Yang, Yuxing; Liang, Weiming; Wang, Xiao (Frontiers in Oncology, 2024)
Introduction Robotic radical hysterectomy (RRH) is a newly developed minimally invasive surgery that has been suggested as a substitute for laparoscopic radical hysterectomy (LRH). This meta-analysis aims to assess the clinical efficacy and safety of robot-assisted radical hysterectomy (RRH) for cervical cancer. Materials and methods A systematic search was conducted in four databases (Medline, Embase, Web of Science, and CENTRAL) for studies comparing the utilization of RRH and LRH in the treatment of cervical cancer. The search included articles published from the inception of the databases up until July 18, 2023. Meta-analyses were conducted to assess several surgical outcomes, including operation time, estimated blood loss, length of hospital stay, pelvic lymph nodes, positive surgical margin, total complications, one-year recurrence rate, one-year mortality, and one-year disease-free survival rate. Results Six studies were included for meta-analysis. In total, 234 patients were in the RRH group and 174 patients were in the LRH group. RRH had significantly longer operative time (MD=14.23,95% CI:5.27~23.20, P=0.002),shorter hospital stay (MD= -1.10,95% CI:-1.43~0.76, P <0.00001),more dissected pelvic lymph nodes(MD=0.89,95%CI:0.18~1.60, P =0.01) and less blood loss(WMD = -27.78,95%CI:-58.69 ~ -3.14, P=0.08, I2 = 80%) compared with LRH. No significant difference was observed between two groups regarding positive surgical margin (OR = 0.59, 95% CI 0.18~2.76, P=0.61), over complications (OR = 0.77, 95% CI, 0.46-1.28, P=0.31), one-year recurrence rate (OR = 0.19, 95% CI 0.03-1.15, P=0.13), one-year mortality rate (OR = 0.19, 95% CI 0.03-1.15, P=0.07) and disease-free survival at one year (OR = 1.92, 95% CI 0.32-11.50, P=0.48). Conclusion RRH is an increasingly popular surgical method known for its high level of security and efficiency. It has many benefits in comparison to LRH, such as decreased blood loss, a higher quantity of dissected pelvic lymph nodes, and a shorter duration of hospitalization. Further multicenter, randomized controlled trials with extended follow-up durations are necessary to conclusively determine the safety and efficacy of RRH, as no significant differences were observed in terms of positive surgical margin, postoperative complications, 1-year recurrence, 1-year mortality, and 1-year disease-free survival. Systematic Review Registration PROSPERO, identifier CRD42023446653